Contemporary Social Theory: Tawhidi Projections (American Journal of Islam and Society, 1994)
IntroductionContemporary social theory is conventionally addresed from withinthe dominant tradition of inquiry. Rarely is it subject to a criticalreflection from beyond its own ken. This is a pity, for the subject matterand scope of social theory go beyond the confines of any exclusivetradition, while its reach and influence in the global context of our timesmerely reinforce its extended compass. Given the fact that the ambitiousclaims made by social theorists about the univetsality of their project arehardly borne out by the reality, any pretensions at exclusivism orhegemony would be as anachronistic as they are morally reprehensible.The gap between the legitimate ambitions for a universally relevant socialtheory and the mdity of a field grounded in its historical coflstral.l lt sandcultural prejudices can be filled only by a critical and constructiveinitiative taken from within the profession to constitute a candid, open,and reflexive self-encounter. The opportuneness for such an initiative isenhanced by its urgency: the discrepancies that follow on the ineptitudeof our social knowledge can only raise doubts about the relevance of ourscience to our social condition.In deploring the tesulting ineptitude and irrelevance, it is possible todo so in the voice of a genemlized subject, the universal "I," for surelythis is one of the ateas of convergence where scholats from different traditionscould agree. The measure of this agreement can only be gaugedby remembering that "a science for the study of society" originally wentbeyond its grounding in scientific reason to its justification in a moralreasoning. And here, regardless of the grounding of that morality, we findanother significant area of convergence for scholars working in different ...